Ekonomi Politik dalam Pembangunan Masyarakat di Era Digital Berbasis Komunitas Religi - Anam, Choirul (Jejaring Administrasi Publik, 2023)
This research explores the relationship between economic, political and religious factors in the context of religion-based digital communities. The Islamic religious community was chosen with the consideration that it is the religion of the majority of the Indonesian population, so that both the real and virtual worlds in the context of community development are definitely dominated by followers of the Islamic religion. This research uses a virtual ethnographic approach and digital critical discourse analysis to investigate the political economic dynamics that influence the development of society in the digital era based on religion. Virtual ethnographic methods allow researchers to investigate the interactions, norms, and values that emerge in the digital space of religious communities. With technological advances, elements of political economy are becoming increasingly visible in societal activities. Critical digital discourse analysis will reveal how political economic narratives are constructed, maintained, or contested in the digital space of religious communities. This research aims to increase our understanding of how political and economic forces are interrelated and how religious values influence the growth of society in the digital era. In addition, the results are expected to help stakeholders create better policies to manage political economic dynamics in the context of faith-based communities in the modern era. Keywords: Community Development, Digital Society, Religious Community